2007
DOI: 10.1584/jpestics.g06-40
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutant acetolactate synthase gene from rice cells, which confers resistance to ALS-inhibiting herbicides

Abstract: A two-point mutated gene of acetolactate synthase (ALS) was isolated from rice cells, which was cultured together with an ALS-inhibiting herbicide, bispyribac-sodium (BS). The mutations involved residues of tryptophan at position 548 to leucine (W548L) and serine at position 627 to isoleucine (S627I). The ALS expressed in Escherichia coli from this gene showed resistance to multiple herbicides including pyrimidinylcarboxylate (PC), sulfonylurea and imidazolinone herbicides, and showed stronger resistance to PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 19 publications
(15 reference statements)
2
38
0
Order By: Relevance
“…In our preceding paper, 3) we generated T 0 transgenic rice plants harboring the W548L/S627I mutated ALS gene through hygromycin selection, and confirmed that heterozygous sequences of endogenous and mutated ALS were detected in genomic DNAs of transgenic plants. One of these plants, W38, showed resistance to BS at 1 kg a.i./ha application.…”
Section: Direct Sequencing Of Cdna Fragments In Transgenic Plantssupporting
confidence: 54%
See 2 more Smart Citations
“…In our preceding paper, 3) we generated T 0 transgenic rice plants harboring the W548L/S627I mutated ALS gene through hygromycin selection, and confirmed that heterozygous sequences of endogenous and mutated ALS were detected in genomic DNAs of transgenic plants. One of these plants, W38, showed resistance to BS at 1 kg a.i./ha application.…”
Section: Direct Sequencing Of Cdna Fragments In Transgenic Plantssupporting
confidence: 54%
“…2) We have isolated a novel mutated ALS gene from rice cells, which confers resistance to PC herbicides. 3,4) Before isolation of this mutated ALS gene, no paper had reported a mutated ALS gene conferring resistance specific to PC herbicides. The mutated gene had two point mutations resulting in W548L/S627I mutations in the ALS protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Double mutations have been found in the rice ALS gene through cell culture using bispyribac-sodium (BS), a PC herbicide (Kawai et al, 2007b). Before isolation of the mutated ALS gene, no paper had reported a mutated ALS gene as conferring resistance to PC herbicides.…”
Section: A Two-point Mutated Rice (Oryza Sativa L) Als Gene Conferrementioning
confidence: 99%
“…Table 1. Mutations in ALS conferring resistance to ALS-inhibiting herbicides (Adapted from Kawai et al, 2007b).…”
Section: A Two-point Mutated Rice (Oryza Sativa L) Als Gene Conferrementioning
confidence: 99%